The construction of the millennial generation religious vision through digital literacy - Erawati, Desi (Journal for the study of religions and ideologies, 2023)
The transformation of society that has led to the advent of digital technology does not necessarily result in the breakdown of the social system. Concerns about a new value system that supplants traditional values among the millennial generation have yet to be substantiated. Furthermore, fears of religious ideology being fueled by computer algorithms have not been observed among millennials in Central Kalimantan. In fact, the participation of the millennial generation in thedigital communication sphere has led to a more open and tolerant religious perspective, rather than a monolithic religious vision. Their observance of theintersection of religion and politics in national discourse has made them uninterested in seeking out or consuming religious and state-related issues. Instead, they tend to favor topics related to human relationships, conveyed in a smooth and engaging manner. This reflects the millennial generation’s desire for a modernand uncomplicated religious life, placing religious issues in the private rather than public sphere. While this study provides a comprehensive picture of the religious vision of millennials in Central Kalimantan, a more nuanced understanding can be achieved by comparing it to similar research in a different and more complex technological context, such as Java. The difference in exposure to digital technology and characteristics of respondents is likely to have an effecton the religious vision of the millennial generation.